2019 Frank Stinchfield Award: A comparison of prosthetic joint infection rates between direct anterior and non-anterior approach total hip arthroplasty: a single institution experience. (June 2019) - Aggarwal, V. K.; Weintraub, S.; Klock, J.; Stachel, A.; Phillips, M.; Schwarzkopf, R.; Iorio, R.; Bosco, J.; Zuckerman, J. D.; Vigdorchik, J. M.; Long, W. J.
Abstract : Aims: We studied the impact of direct anterior (DA) versus non-anterior (NA) surgical approaches on prosthetic joint infection (PJI), and examined the impact of new perioperative protocols on PJI rates following all surgical approaches at a single institution. Patients and Methods: A total of 6086 consecutive patients undergoing primary total hip arthroplasty (THA) at a single institution between 2013 and 2016 were retrospectively evaluated. Data obtained from electronic patient medical records included age, sex, body mass index (BMI), medical comorbidities, surgical approach, and presence of deep PJI. There were 3053 male patients (50.1%) and 3033 female patients (49.9%). The mean age and BMI of the entire cohort was 62.7 years (18 to 102, sd 12.3) and 28.8 kg/m 2 (13.3 to 57.6, sd 6.1), respectively. Infection rates were calculated yearly for the DA and NA approach groups. Covariates were assessed and used in multivariate analysis to calculate adjusted odds ratios (ORs) for risk of development of PJI with DA compared with NA approaches. In order to determine the effect of adopting a set of infection prevention protocols on PJI, we calculated ORs for PJI comparing patients undergoing THA for two distinct time periods: 2013 to 2014 and 2015 to 2016. These periods corresponded to before and after we implemented a set of perioperative infection protocols. Results: There were 1985 patients in the DA group and 4101 patients in the NA group. The overall rate of PJI at our institution during the study period was 0.82% (50/6086) and decreased from 0.96% (12/1245) in 2013 to 0.53% (10/1870) in 2016. There were 24 deep PJIs in the DA group (1.22%) and 26 deep PJIs in the NA group (0.63%; p = 0.023). After multivariate analysis, the DA approach was 2.2 times more likely to result in PJI than the NA approach (OR 2.2 (95% confidence interval 1.1 to 3.9); p = 0.006) for the overall study period. Conclusion: We found a higher rate of PJI in DA versus NA approaches. Infection prevention protocols such as use of aspirin, dilute povidone-iodine lavage, vancomycin powder, and Gram-negative coverage may have been positively associated with diminished PJI rates observed for all approaches over time. Cite this article: Bone Joint J 2019;101-B(6 Supple B):2–8.